Micro Media Industries : Hmong American Media Innovation in the Diaspora - Lopez, Lori Kido (Book collections on Project MUSE., 2021)
"With the rise of digital tools used for media entrepreneurship, media outlets staffed by only one or two individuals and targeted to niche and super-niche audiences are developing across a wide range of platforms. Minority communities such as immigrants and refugees have long been pioneers in this space, operating ethnic media outlets with limited staff and funding to produce content that is relevant and accessible to their specific community. Micro Media Industries explores the specific case of Hmong American media, showing how an extremely small population can maintain a robust and thriving media ecology in spite of resource limitations and an inability to scale up. Based on six years of fieldwork in Hmong American communities in Wisconsin, Minnesota, and California, it analyzes the unique opportunities and challenges facing Hmong newspapers, radio, television, podcasts, YouTube, social media, and other emerging platforms. It argues that micro media industries, rather than being dismissed or trivialized, ought to be held up as models of media innovation that can counter the increasing power of mainstream media"--